Optimum capacitor placement and sizing for distribution system based on an improved voltage stability index - Aman, M.M.; Jasmon, G.B.; Bakar, A.H.A.; Mokhlis, Hazlie (Praise Worthy Prize, 2012)
With the advent of restructuring in power system and the recent power blackouts, the importance of reactive power support to the system has increased. Shunt capacitor is normally placed in the distribution system for reactive power support and voltage stability. In this paper, an index is proposed considering the effect of shunt capacitor on system voltage stability and referred as Reactive power compensation based Voltage Stability Index (RVSI). The index is based on finding the most sensitive voltage bus in the distribution system. An algorithm is also proposed, based on RVSI, for optimum shunt capacitor placement in the distribution system. The proposed algorithm is tested on 12-bus, 33-bus and 69-bus radial distribution networks. The test results are also compared and found in close agreement with the existing Golden Section Search (GSS) algorithm.